Lucky Luke. 15, The Daltons in the blizzard - Goscinny, 1926-1977.; Morris, 1923-; Spear, Luke (Canterbury, Kent [England] : Cinebook, 2009)
Lucky Luke and his dog Rin Tin Can head north to Canada to recapture the Dalton brothers who escaped from a Texas jail.
First published: Paris: Dargaud Editeur, c1971, under title: Lucky Luke: Les Daltons dans le blizzard.
Spine title.
Translated from the French.
3.9
3-6.
3-6
Keywords: Dalton Gang -- Comic books, strips, etc. -- Juvenile fiction; Dalton Gang -- Fiction; Dalton Gang -- Comic books, strips, etc. -- Fiction; Cowboys -- Comic books, strips, etc -- Juvenile fiction; Lucky Luke (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cowboys -- Fiction; Lucky Luke (Fictitious character) -- Fiction; Comic books, strips, etc; Cowhands -- Comic books, strips, etc -- Fiction; Lucky Luke (Fictional character) -- Comic books, strips, etc -- Fiction; Western comic books, strips, etc; West (U.S.) -- Comic books, strips, etc -- Juvenile fiction; West (U.S.) -- Fiction; West (U.S.) -- Comic books, strips, etc -- Fiction; Graphic novels; Western comic books, strips, etc